PENGARUH KUALITAS PELAPORAN KEUANGAN TERHADAP ASIMETRI INFORMASI DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI PADA PERUSAHAAN MANUFAKTUR DI BEI - ARI BUDI SANTOSO (Universitas Katolik Widya Mandala Surabaya, 2012)
The study entitled Effect Of Quality Financial Reporting Information Asymmetry By Company Size As Moderating In Manufacture a Registered Company in Indonesia Stock Exchange aims to examine the effect of the quality of financial reporting of information asymmetry is moderated by firm size (size). This study uses a variable value relevance as a proxy for the in measuring the quality of financial reporting and the use of proxy-bid-ask spread for the information asymmetry variables. The data used in this study were 76 companies manufacturing a listing on the Indonesia Stock Exchange during the period 2006-2010. Data analysis technique used to test the assumption of classical and regression analysis with the help of this research program SPSS. The result known that the quality of financial reporting are moderated company size had no significant effect to information asymmetry.